2022
DOI: 10.1371/journal.pone.0273515
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with routine vaccination card retention among children aged 0–59 months in Yaounde-Cameroon: A cross-sectional survey

Abstract: Background The routine vaccination card is an important health record for children, but recent findings suggest that vaccination card retention in Cameroon is low, varying from 29%-53%. The aim of this study was to assess factors associated with children’s routine vaccination card retention in Cameroon. Methods This cross-sectional survey was conducted in Yaoundé in November 2021, targeting children aged 0–59 months. Participants were selected using a 2-stage systematic cluster sampling in which households w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…In this study, factors associated with the non-availability of vaccination cards were maternal age below 25 years and the mother having a paid job. A study recently conducted in Yaoundé (Cameroon) corroborate our results 30 . It suggests that mothers who are employed have little time to follow their children’s immunization and might occasionally delegate this to a third party (say a family member), with vaccination card getting missed consequently 30 .…”
Section: Discussionsupporting
confidence: 92%
“…In this study, factors associated with the non-availability of vaccination cards were maternal age below 25 years and the mother having a paid job. A study recently conducted in Yaoundé (Cameroon) corroborate our results 30 . It suggests that mothers who are employed have little time to follow their children’s immunization and might occasionally delegate this to a third party (say a family member), with vaccination card getting missed consequently 30 .…”
Section: Discussionsupporting
confidence: 92%
“…A vaccination card was defined as any document given by a healthcare provider stating the vaccination status of an eligible child [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted by Wagner reported retention rate of 23.3% in Nigeria, 49.6% in Angola, 29.5% in Ethiopia, and 20.7% in Democratic Republic of Congo [ 12 ]. Studies conducted in Yaounde-Cameroon [ 13 ] and Senegal [ 14 ] also reported retention rates of 24% and 86.6% respectively. While child age and maternal employment were found to be negatively associated with card retention, being a girl child, living in rich household and respondent being the biological parent of the child were positively associated with card retention in Yaounde-Cameroon [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A vaccination card was defined as any document given by a healthcare provider stating the vaccination status of an eligible child [17].…”
Section: Operational Definitionsmentioning
confidence: 99%